Influence of Biochar, Mulch and PPFM on Stress Physiological Parameters of Cotton under Moisture Stressed Condition - Kannan, V.; Srinivasan, G.; Sivakumar, T. (International Journal of Bio-resource and Stress Management, 2019)
The field experiments were conducted at Agricultural College and Research Institute, Madurai during summer and winter irrigated cotton seasons of 2016 and 2016-17. Experiments were laid out in split plot design with three replications. Moisture regimes were assigned to the main plots viz., Irrigation at IW/CPE ratio 0.4 and 0.8. The subplot comprises with moisture stress management practices viz., Cotton stalk biochar @ 5 t ha-1, Cotton stalk biochar @ 5 t ha-1+Crop residue mulch @ 5 t ha-1, Cotton stalk biochar @ 5 t ha-1+Crop residue mulch @ 5 t ha-1 and PPFM @ 500 ml ha-1 on 75 and 90 DAS, Prosopis biochar @ 5 t ha-1, Prosopis biochar @ 5 t ha-1+Crop residue mulch @ 5 t ha-1, Prosopis biochar @ 5 t ha-1+crop residue mulch @ 5 t ha-1 and PPFM @ 500 ml ha-1 on 75 and 90 DAS and Control. The stress physiological parameters observed viz., Relative leaf water content, Chlorophyll stability index and Leaf accumulated proline were greatly influenced during moisture stress period. The Maintenance of higher relative water content helps in sustaining the photosynthetic capacity of plants which ultimately contributes to higher yield. In this study higher relative leaf water content, chlorophyll stability index, lower leaf accumulated proline and higher yield of cotton was recorded in irrigation at IW/CPE to 0.8 and Prosopis biochar @ 5 t ha-1+crop residue mulch @ 5 t ha-1 and PPFM @ 500 ml ha-1.